1985
DOI: 10.1002/jpln.19851480102
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen zur Silizium‐Versorgung von Kulturpflanzen in Schleswig‐Holstein

Abstract: Zur Untersuchung der Siliziumversorgung und des Einflusses Silizium‐haltiger Dünger auf die Mineralstoffzusammensetzung von Kulturpflanzen wurden in Schleswig‐Holstein Felderhebungsuntersuchungen und Feldversuche zu Getreide und Raps durchgeführt. Getreidepflanzen wiesen im Gegensatz zu Rapspflanzen eine deutliche Differenzierung der Silizium‐Gehalte nach den Naturräumen des Landes auf. Zu Schoßbeginn wurden auf den Podsolen der Geest in Getreidepflanzen durchschnittlich 2,5 mg Si/g TS, auf den Braunerden des … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

1985
1985
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…For example, in rice, the grain typically contains 0.2 g Si kg –1 , the bran 20 g Si kg –1 , straw 60 g Si kg –1 , rice husk 110 g Si kg –1 and rice joints (at the base of the grain) 160 g Si kg –1 (calculated from van Soest, 2006, and rounded to equivalent significant figures). Variation of plant Si content with soil type is reported by Schnug & von Franck (1985) for wheat, barley and oats in Schleswig-Holstein (Germany), reporting the lowest concentrations for crops grown on podzol (2.5 g Si kg –1 ), intermediate concentrations on a brown earth (5.9 g Si kg –1 ) and highest concentrations on a marsh soil (11.5 g Si kg –1 ).…”
Section: Mineral Weatheringmentioning
confidence: 84%
See 1 more Smart Citation
“…For example, in rice, the grain typically contains 0.2 g Si kg –1 , the bran 20 g Si kg –1 , straw 60 g Si kg –1 , rice husk 110 g Si kg –1 and rice joints (at the base of the grain) 160 g Si kg –1 (calculated from van Soest, 2006, and rounded to equivalent significant figures). Variation of plant Si content with soil type is reported by Schnug & von Franck (1985) for wheat, barley and oats in Schleswig-Holstein (Germany), reporting the lowest concentrations for crops grown on podzol (2.5 g Si kg –1 ), intermediate concentrations on a brown earth (5.9 g Si kg –1 ) and highest concentrations on a marsh soil (11.5 g Si kg –1 ).…”
Section: Mineral Weatheringmentioning
confidence: 84%
“…For example, in rice, the grain typically contains 0.2 g Si kg -1 , the bran 20 g Si kg -1 , straw 60 g Si kg -1 , rice husk 110 g Si kg -1 and rice joints (at the base of the grain) 160 g Si kg -1 (calculated from van Soest, 2006, and rounded to equivalent significant figures). Variation of plant Si content with soil type is reported by Schnug & von Franck (1985) for wheat, barley and oats in Fig. 1.…”
mentioning
confidence: 99%
“…This observation is in line with the findings by Schuchrschubel and Heinemunn (1968). on the Si concentrations in soil solutions, and with the investigation by Schnug and v. Frunck (1985). who found no significant correlation between the Si concentration in wheat and soil pH.…”
Section: Dependence On Soil Phmentioning
confidence: 92%
“…One of these factors probably is the concentration of primary and secondary silicates in the soil. For cereals it has been shown that plants growing on soils poor in easily weatherable silicates have low Si concentrations (Wagner, 1940;Schnug and v. Frunck, 1985).…”
Section: Dependence On Other Soil Parametersmentioning
confidence: 99%
“…Untersuchungen aus Schleswig-Holstein zeigen jedoch, daB die Schwefel-Versorgung von Winterraps auf 40-50 % der Anbauflachen zur Produktion von Hochstertragen bis zu 50 d t h a Rapskorn unzureichend ist (Schnug et al, 1984) und durch Anwendung schwefelhaltiger Dungemittel auch im Getreidebau Ertragssteigerungen auftreten konnen (Schnug, 1982). Da schwefelhaltige Handelsdunger in der Landwirtschaft kaum noch eingesetzt werden und intensive Ackerbaubetriebe meist viehlos wirtschaften, erfolgt die Schwefel-Zufuhr auf solchen Standorten allein aus der Atmosphare.…”
unclassified